2015
DOI: 10.1159/000441089
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Changes in Two Leber's Hereditary Optic Neuropathy Pedigrees: 12-Year Follow-Up

Abstract: We are presenting two Leber's hereditary optic neuropathy (LHON) pedigrees with abnormal magnetic resonance imaging (MRI) and proton magnetic resonance spectroscopy (H-MRS) findings but without neurological manifestation associated with LHON. The study included 14 LHON patients and 41 asymptomatic family members from 12 genealogically unrelated families. MRI showed white matter involvement and H-MRS exhibited metabolic anomalies within 12 LHON families. Main outcome measures were abnormal MRI and H-MRS finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Approximately 67.9% of LHON cases present with high-intensity optic chiasm and bilateral optic tracts on T2-weighted MRI; 12 however, 4.1% to 10% of GC cases also present with such findings. 13–15 Patients with LHON infrequently present with white matter changes on MRI, 10 , 16 , 17 but none so far have presented with diffuse infiltrates, such as the present case.…”
Section: Discussionmentioning
confidence: 54%
“…Approximately 67.9% of LHON cases present with high-intensity optic chiasm and bilateral optic tracts on T2-weighted MRI; 12 however, 4.1% to 10% of GC cases also present with such findings. 13–15 Patients with LHON infrequently present with white matter changes on MRI, 10 , 16 , 17 but none so far have presented with diffuse infiltrates, such as the present case.…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, up-todate diagnostic techniques have allowed for a much earlier detection of the disease (38). Differential diagnosis should be performed in order to rule out other possible causes with similar clinical signs and symptoms (1,39,40).…”
Section: Clinical Characteristics: Children Versus Adultsmentioning
confidence: 99%
“…This class of medication reduces relapses in adults by as much as 30% (6,40). These drugs, with anti-inflammatory and immunomodulatory effects, significantly reduce the frequency and severity of clinical relapses and disease activity, as shown by MRI of the brain, as well as reduce the degree of disability (39). Results for interferon beta-1a application in young children (aged 2-11 years) versus adolescents (aged 12-17 years) have shown that the safety profile is similar.…”
Section: First-line Immunomodulatory Therapymentioning
confidence: 99%
“…The most common diseases that must be taken into account before establishing a definitive diagnosis of MS are presented in Fig. 1 [1, 39, 40].
Fig.
…”
Section: Etiologymentioning
confidence: 99%